Visualizing large trees and graphs using a 3D cone tree layout - Nadeau, David Robert (2008)
Tree and graph structures are often visualized as 2D linear tree diagrams with labeled dots and connecting lines. But when the data grows beyond several dozen nodes, these diagrams become large and awkward. This article looks at a 3D Cone Tree scheme for visualizing trees and graphs with several thousand nodes. I outline the layout algorithm, show examples, and discuss strengths and weaknesses for the approach.